A survey of various FE models with conceptual diagrams for linear analysis - Radwańska, Maria (Computer Assisted Methods in Engineering and Science, 2022)
In the paper a general survey of existing finite element (FE) models is presented using a conceptual description in diagram form, which was initiated in paper [1] . The analysis is focused on the description of FE models, which is uniform in its concept but specific for each FE type. All FE models are associated with certain variational principles (and their stationarity conditions) in their original or modified versions. The diagrams are used to visualize the equations which are satisfied inside an individual FE and on interelement boundaries. The use of conceptual diagrams is very convenient in the presentation of finite element method (FEM), it simplifies the understanding and teaching of this method.